2008
DOI: 10.1111/j.1365-3083.2008.02121.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for De Novo Expression of Thymic Insulin by Peripheral Bone Marrow‐derived Cells

Abstract: Thymic expression of insulin has been suggested to play a major role in negative selection of autoreactive T cells and tolerance induction against pancreatic β cells. Furthermore, the expression of insulin in peripheral antigen‐presenting cells (APC) has been clearly demonstrated but whether thymic negative selection and tolerance induction also depends on peripheral influx of self‐antigens (Ag) remains to be conclusively demonstrated. In this study, we wanted to test whether peripheral influx of insulin expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Although we did not observe the presence of Ins2 transcripts in bone marrow‐derived thymic APCs under our experimental conditions (Figure 1B), the residual (<10%) insulin transcripts observed in the ID‐TEC thymus might come from these bone marrow‐derived cells under the hyperglycemic conditions of the diabetic ID‐TEC mice. Indeed, there are a number of reports showing elevation of ectopic insulin expression in bone marrow‐derived cells under these abnormal conditions (Kojima et al , 2004; Carlsen and Cilio, 2008). Furthermore, overexpression of autoantigens, including insulin, in bone marrow‐derived APCs has been shown to attenuate or prevent autoimmune diabetes progression in NOD mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not observe the presence of Ins2 transcripts in bone marrow‐derived thymic APCs under our experimental conditions (Figure 1B), the residual (<10%) insulin transcripts observed in the ID‐TEC thymus might come from these bone marrow‐derived cells under the hyperglycemic conditions of the diabetic ID‐TEC mice. Indeed, there are a number of reports showing elevation of ectopic insulin expression in bone marrow‐derived cells under these abnormal conditions (Kojima et al , 2004; Carlsen and Cilio, 2008). Furthermore, overexpression of autoantigens, including insulin, in bone marrow‐derived APCs has been shown to attenuate or prevent autoimmune diabetes progression in NOD mice.…”
Section: Discussionmentioning
confidence: 99%
“…Using this very stringent model, we investigated the potential contribution to self‐tolerance of NOD BM‐derived cells, as CD11c + cells are the only cells so far shown to naturally express Ins2 in both thymus and peripheral lymphoid tissues. Moreover, experimental data show that BM‐derived cells contribute to Ins2 expression in the thymus in the absence of Ins2 expression in the mTEC [37]. Studies in transgenic mice have also shown that TSA expression by BM‐derived cells can be tolerogenic and results in activation induced cell death in the periphery [24].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with an earlier study that showed restoration of Ins2 mRNA expression in the thymus when this was transplanted under the kidney capsule. [37].…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not observe the presence of Ins2 transcripts in bone marrow-derived thymic APCs under our experimental conditions (Figure 1B), the residual (o10%) insulin transcripts observed in the ID-TEC thymus might come from these bone marrow-derived cells under the hyperglycemic conditions of the diabetic ID-TEC mice. Indeed, there are a number of reports showing elevation of ectopic insulin expression in bone marrow-derived cells under these abnormal conditions (Kojima et al, 2004;Carlsen and Cilio, 2008). Furthermore, overexpression of autoantigens, including insulin, in bone marrow-derived APCs has been shown to attenuate or prevent autoimmune diabetes progression in NOD mice.…”
Section: Discussionmentioning
confidence: 99%
“…As ectopic insulin expression has been reported in BM-derived APCs within the thymus [23,24,30], we also examined EYFP expression in thymic APCs. As shown in Fig.…”
Section: Tissue-specific Deletion Of the Mouse Ins2 Gene In Bm-derivementioning
confidence: 99%